Peran Dinas Perhubungan Kabupaten Blitar Dalam Meningkatkan Retribusi Parkir Konvensional Di Wilayah Kabupaten Blitar - Adenanthera Lesmana Dewa; Dani Yusuf Maulana; Wasi Sumarsono (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2021)
Parking retribution is one of the managed potentials to be used as a source of regional revenue originating from within the region, it becomes a benchmark in assessing the level of regional original income obtained by the region. The proceeds from the revenue will be allocated for the development of the area itself, especially in building facilities and facilities for repairing parking lots which have an impact on governance in the implementation of parking that goes well and does not interfere with other road users. The implementation of parking fees in Blitar Regency is regulated in Blitar Regency Regional Regulation No. 2 of 2018 Business Services Retribution is a levy for parking services on land or on the side of public roads. Analysis of the data used in this study is descriptive analysis and quantitative analysis, the data were analyzed using multiple linear regression analysis with the help of (software) Statistical Package For Social Science (SPSS) version 25. The results of the study by partially testing the t-test hypothesis showed that the characteristics of parking attendants, facilities, service quality and supervision had a positive and significant effect on increasing parking fees. Based on the tests that have been carried out, the linear regression equation is Y -1.735 + 0.291 X1 + 0.256 X2 + 0.247 X3 + 0.335 X4 + µ.